Increased Adherence to the Mediterranean Diet after Lifestyle Intervention Improves Oxidative and Inflammatory Status in Patients with Non-Alcoholic Fatty Liver Disease - Margalida Monserrat-Mesquida; Magdalena Quetglas-Llabrés; Cristina Bouzas; Sofía Montemayor; Catalina M. Mascaró; Miguel Casares; Isabel Llompart; Lucía Ugarriza; J. Alfredo Martínez; Josep A. Tur; Antoni Sureda (MDPI AG, 2022)
Background: A Mediterranean diet (MedDiet) is recommended as a therapy for non-alcoholic fatty liver disease (NAFLD) because there is no specific pharmacological treatment for this disease. Objective: To assess the relationship between the adherence to the Mediterranean diet and the intrahepatic fat content (IFC), levels of oxidative stress, and inflammation biomarkers after a 6-month lifestyle intervention in NAFLD patients. Methods: Patients diagnosed with NAFLD (n = 60 adults; 40-60 years old) living in the Balearic Islands, Spain, were classified into two groups, according to the adherence to the MedDiet after 6 months of lifestyle intervention. Anthropometry, blood pressure, IFC, maximal oxygen uptake, and pro/antioxidant and inflammatory biomarkers were measured in plasma and in PBMCs before and after the intervention. Results: Reductions in weight, body mass index, IFC, blood pressure levels, circulating glucose, glycosylated hemoglobin, and markers of liver damage-aspartate aminotransferase (AST), alanine aminotransferase (ALT), gamma-glutamyl transferase (GGT), and cytokeratin 18 (CK-18)-were observed after the intervention. The highest reductions were observed in the group with the best adherence to the MedDiet. A significant improvement in cardiorespiratory fitness was also observed in the group with a higher adherence. The activities of catalase in plasma and catalase and superoxide dismutase in blood mononuclear cells increased only in the group with a higher adherence, as well as the catalase gene expression in the blood mononuclear cells. The plasma levels of malondialdehyde and myeloperoxidase decreased, and resolvin-D1 increased in both groups after the intervention, whereas interleukin-6 levels decreased only in the group with a higher adherence to the MedDiet. Conclusions: A greater adherence to the MedDiet is related to greater improvements in IFC, cardiorespiratory fitness, and pro-oxidative and proinflammatory status in NAFLD patients after a 6-month nutritional intervention based on the MedDiet.